A novel TMR based triaxial eddy current test probe for any orientation crack detection. (August 2021) - Betta, G.; Ferrigno, L.; Laracca, M.; Rasile, A.; Sangiovanni, S.
Highlights: Triaxial eddy current testing probe to improve the defect detection capability. Crack detection sensitivity for any defect orientation. TMR based triaxial magnetic sensor for ECT applications. Experimental uncertainty model of TMR sensors to be implemented in simulations. Abstract: The paper proposes the development, the analysis, and the experimental validation of a novel probe for Eddy Current (EC) Non-Destructive Testing especially thought to warrant good signal to noise ratios in the detection of thin defects when low excitation currents are adopted and whatever the orientation of the probe respect to the orientation of the defect. The probe is based on a simple double coil excitation, that generate a single direction EC flow, and adopts three magnetic sensors that form a triaxial magnetic sensor. Other main contributions of this paper are: i) performance analysis of an EC triaxial probe carried out in simulation environment that considers the measurement uncertainty of the magnetic sensors; ii) an experimental campaign that allow evaluating the performance of the realized probe; iii) a comparison between simulated and experimental results that prove the goodness of the proposed approach.